2009
DOI: 10.1021/es9001604
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Plasma Concentrations of Perfluorooctanesulfonate and Brominated Organic Compounds in Nunavik Inuit Adults (Canada)

Abstract: Perfluorooctanesulfonate (PFOS) and brominated organic compounds (BOCs) have been found in biota and humans worldwide with levels of BOCs being the highest in North America. PFOS and BOC exposure of remote populations that consume species of a marine food web for their subsistence has seldom been investigated. In 2004, we determined the concentrations of these contaminants in 883 Nunavik Inuit adults from the Canadian Arctic and investigated the demographic and dietary factors associated with them. Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…In a study of BFRs in Canadian Inuit from Nunavik, Quebec, plasma samples were found to contain a geometric mean TBP concentration of 58 ng/L or approximately 9.4 ng/g lw [127]. These concentrations were somewhat higher than those of BDE-47 and -153 and in the same range as those found in Norway.…”
Section: Humansmentioning
confidence: 88%
“…In a study of BFRs in Canadian Inuit from Nunavik, Quebec, plasma samples were found to contain a geometric mean TBP concentration of 58 ng/L or approximately 9.4 ng/g lw [127]. These concentrations were somewhat higher than those of BDE-47 and -153 and in the same range as those found in Norway.…”
Section: Humansmentioning
confidence: 88%
“…BFRs were also evaluated in Norwegian individuals working in electronics dismantling facilities, where 2,4,6-TBP was measured in plasma ranging from 0.17 to 81 ng/g lipid 17 . In a study measuring BFRs in a Canadian Inuit population from Nunavik, Quebec, plasma samples contained a geometric mean 2,4,6-TBP concentration of 9.4 μg/kg lipid, however, these concentrations were not correlated with PBDE concentrations 18 . Finally, Qiu et al measured mean 2,4,6-TBP concentrations of 5.6 ng/g lipid in fetal plasma and 0.8 ng/g lipid in maternal plasma 19 .…”
Section: Introductionmentioning
confidence: 94%
“…Concentrations and distributions of PBDEs in the environment were well documented in North America (Dallaire et al 2009), Europe (Jaraczewska et al 2006, Roosens et al 2010, Australia (Besis and Samara 2012) and Asia (Hong et al 2010). Yet, there is little information about the exposure levels of PBDEs in Chinese lakes (Zhou et al 2012).…”
Section: Introductionmentioning
confidence: 99%